Analysis of Robocall Attacks, Methods of Protection Against this Threat - Alekberova, T.Sh.; Haciyev, R.M. (Herald of Azerbaijan Engineering Academy, 2025)
Cybercrime is recognized as any crime related to computers and the internet. It involves attacks on information about individuals, companies, or governments. When individuals are the primary target, their computers are used as tools in cybercrime. Cybercrimes also include traditional crimes committed with internet access. For example, telemarketing, internet fraud, identity theft, and credit card fraud are current examples of cybercrimes. In other words, cybercrime can be classified as an act of violence carried out using any device with internet access. Billions of robocalls are made around the world every month. Thanks to technology, telemarketers and scammers can make robocalls over the internet. Some robocalls may offer useful information, such as appointment reminders or canceled flights. However, they primarily aim to sell you something, and many of them are scams. When these calls are made, the caller often hides behind various excuses. The article analyzes the current cyber threat and analyzes ways to protect against this attack.